ANTIMICROBIAL ACTIVITY OF CHITOSAN 2% AND OXYGENIZING DENTURE CLEANSER ON PROHIBITING STREPTOCOCCUS MUTANS GROWTH AT ACRYLIC HEAT-CURED RESINS PLATE: EFEK ANTIMIKROBA KITOSAN 2% DAN PEMBERSIH GIGI TIRUAN BEROKSIDA DALAM MENGHAMBAT PERTUMBUHAN STREPTOCOCCUS MUTANS PADA LEMPENG RESIN AKRILIK POLIMERISASI PANAS - Evelyna, Angela; Sutanto, Dahlia; Nadapdap, Astuti (TALENTA, 2017)
Heat-cured acrylic denture base-plate may act as reservoir for Streptococcus mutans (all species name must be in italics) colonies, this condition may lead to denture stomatitis. One of denture cleansing method that frequently used is by immersion (of what?) in oxygenizing denture cleansers that has several disadvantages such as high cost and biocompatibility issue regarding chemical synthetic component of the solution. Chitosan is a natural compound that has antibacterial nature. The most commonly percentage of chitosan used for biomedical purposes is 2%. The objective of this study is to evaluate the antimicrobial effectivity of chitosan 2% on acrylic heat-cured plates and compare it with oxygenizing denture cleansers. Aquadest was used as control. Fifteen acrylic heat-cured plates (10 x10 x 2 mm) immersed in Streptococcus mutans suspensions at temperature 37Â°C for 48 hours of 3 different solutions. The solutions were vortexed and put into (Brain Heart Infusion Agar) medium. Streptococcus mutans colonies were counted manually. The result shows, that Streptococcus mutans colonies on aquadest group was 269.75 CFU/plate, followed by oxygenizing denture cleanser with 11 CFU/plate), and chitosan 2% group with 0.4 CFU/plate, respectively. Data were analysed with Kruskal-Wallis non-parametric test followed by Mann-Whitney test shows of p=0.012 (p<0.05). There were no statistically significant different of antimicrobial activity between chitosan 2% and oxygenizing denture cleanser. The result demonstrated that chitosan 2% solution was more effective to prohibit the growth of Streptococcus mutans colonies on acrylic heat cured plates, however a statistically significant difference between the two groups was not observed.